Implementation Of The Balanced Scorecard In Improving The Performance Of Private Universities - Ruhviyanti, Novi; Wasliman, Iim; Hanafiah, Hanafiah; Tejawiani, Ida (International Journal of Educational Research & Social Sciences, 2022)
The role of private universities in improving quality must accommodate all aspects of the performance of the tridharma of higher education. The rapid development of higher education institutions must be ready to change, changes that occur in the global business environment also trigger the increasing intensity of competition between higher education service providers, so that each higher education service provider will try to offer high performance higher education services. The purpose of this research is to see how far the implementation of BSC in improving the performance of private universities. Specifically, this study describes four perspectives, including: (1) financial perspective, (2) customer perspective, (3) internal business process perspective (4) learning and growth perspective.This study uses a descriptive method with a qualitative approach and data collection by conducting observations, interviews, and documentation studies. From the research results indicate that the implementation of the BSC has been applied in a systematic, measurable and planned manner so that the Vision, Mission and objectives are achieved. In implementation there is a balance between financial and non-financial.